On the zonal and meridional eddy flux of energy components o the troposphere over the Arabian Sea during the onset phase of SW monsoon (MAUSAM, 1983)
The rawinsonde data collected during the Arabian Sea phase of the MONEX- 79 have been utilized to study the zonal and meridional eddy fluxes of dry static and moist static energy of the troposphere over the Arabian Sea during the onset phase of SW-Monsoon, The study reveals that .the zonal eddy flux of dry static energy is Irregularly distributed with height whereas the eastward eddy flux of moist static energy becomes dominant during the onset phase of monsoon having maximum value within the layer 900-600 mb. There exists a well-marked magnitudinal difference between the zonal eddy fluxes of dry static and moist static energy due mainly to the contribution of eddy flux of latent heat with increasing monsoon activity. To the east of 60° E, the maximum southward eddy flux of dry static energy at 700 mb roughly along 7oN shows the tendency to be northward and the northward eddy flux of moist static energy along 7° N and below extends to 700 mb or further downward with the advancement of SW-Monsoon.